Insomnia and Depression - Bidirectional Cause and Effect: A Literature Review - Yohanes Febrianto (Scientia Psychiatrica, 2021)
Insomnia is a health problem that is very often experienced by patients and can have an impact on the emergence of psychiatric problems, such as depression. On the other hand, patients with depression may develop insomnia during this phase of the illness. This shows that there is a bi-directional relationship that must be described in order to understand the diagnosis and management of the two cases. Through the review of this article, a theoretical review of the relationship between the two in general and theoretical in order to understand each aspect is presented because the management of the two is closely related to each other.